Utilization of sexual reproductive health services among public service vehicle operators in Nairobi City County, Kenya - Oenga, Davis; Mugo, Judy; Kiplalom, Rosebella (International Journal Of Community Medicine And Public Health, 2023)
Background: Public service vehicle operators and owners are a susceptible demographic in need of specialized treatments due to their high vulnerability to these problems. The primary purpose of this research was to learn on the utilization of sexual reproductive health services (SRH) among public service vehicle (PSV) operators in Nairobi County use sexual and reproductive health care services. Methods: A descriptive cross-sectional study design was adopted for the study. The research approach used both qualitative and quantitative techniques. Operators at bus terminals made up the bulk of the research population. The Cochran’s formula was used to precisely estimate a sample’s contribution to a population, and the sampling estimate had a variance (margin of error) of 0.5. Results: The logistic regression model results showed that, after controlling for demographics, female PSV operators were 97% more likely to use SRH services on at least four separate occasions than their male counterparts (95% CI (0.21 to 0.96), p=0.015). When controlling for age, marital status, and education, PSV operators from universities are 75% more likely to use SRH services than those from primary schools (95% CI (1.12 to 0.75), p=0.001), and those from secondary schools are 68% more likely to use SRH services than those from primary schools (95% CI (0.241 to 0.679), p=0.004). Conclusions: This study concluded that, the utilization of SRH services among PSV is at 36.6%, married PSV operators utilize sexual reproductive health services was more than unmarried PSV operators. Age, level of education and employment status are determinants to utilization of the selected sexual reproductive health services.